Pathogenic Autoimmunity in Atherosclerosis Evolves From Initially Protective Apolipoprotein B100–Reactive CD4+ T-Regulatory Cells. Issue 13 (29th September 2020) - Wolf, Dennis; Gerhardt, Teresa; Winkels, Holger; Michel, Nathaly Anto; Pramod, Akula Bala; Ghosheh, Yanal; Brunel, Simon; Buscher, Konrad; Miller, Jacqueline; McArdle, Sara; Baas, Livia; Kobiyama, Kouji; et al.
Abstract : Background: Throughout the inflammatory response that accompanies atherosclerosis, autoreactive CD4 + T-helper cells accumulate in the atherosclerotic plaque. Apolipoprotein B100 (apoB), the core protein of low-density lipoprotein, is an autoantigen that drives the generation of pathogenic T-helper type 1 (TH 1) cells with proinflammatory cytokine secretion. Clinical data suggest the existence of apoB-specific CD4 + T cells with an atheroprotective, regulatory T cell (Treg ) phenotype in healthy individuals. Yet, the function of apoB-reactive Tregs and their relationship with pathogenic TH 1 cells remain unknown. Methods: To interrogate the function of autoreactive CD4 + T cells in atherosclerosis, we used a novel tetramer of major histocompatibility complex II to track T cells reactive to the mouse self-peptide apo B978-993 (apoB + ) at the single-cell level. Results: We found that apoB + T cells build an oligoclonal population in lymph nodes of healthy mice that exhibit a Treg -like transcriptome, although only 21% of all apoB + T cells expressed the Treg transcription factor FoxP3 (Forkhead Box P3) protein as detected by flow cytometry. In single-cell RNA sequencing, apoB + T cells formed several clusters with mixed TH signatures that suggested overlapping multilineage phenotypes with pro- and anti-inflammatory transcripts of TH 1, T helper cell type 2 (TH 2), and T helper cell type 17 (TH 17), and of follicular-helper T cells. ApoB + T cells were increased in mice and humans with atherosclerosis and progressively converted into pathogenic TH 1/TH 17-like cells with proinflammatory properties and only a residual Treg transcriptome. Plaque T cells that expanded during progression of atherosclerosis consistently showed a mixed TH 1/TH 17 phenotype in single-cell RNA sequencing. In addition, we observed a loss of FoxP3 in a fraction of apoB + Tregs in lineage tracing of hyperlipidemic Apoe –/– mice. In adoptive transfer experiments, converting apoB + Tregs failed to protect from atherosclerosis. Conclusions: Our results demonstrate an unexpected mixed phenotype of apoB-reactive autoimmune T cells in atherosclerosis and suggest an initially protective autoimmune response against apoB with a progressive derangement in clinical disease. These findings identify apoB autoreactive Tregs as a novel cellular target in atherosclerosis. Abstract : Supplemental Digital Content is available in the text.